Pengaruh Ice Breaking Terhadap Keaktifan Belajar Siswa Pendidikan Agama Kristen (PAK) Kelas VIII SMP Negeri 1 Sipoholon Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Meta Rosianna; Masniar Hernawaty Sitorus; Rida Gultom; Goklas J. Manalu; Raikhapoor Raikhapoor (International Forum of Researchers and Lecturers, 2024)
This research aims to determine the magnitude of the influence of Ice Breaking on the Learning Activeness of Christian Religious Education (PAK) of Class VIII Students of SMP Negeri 1 Sipoholon for the 2023/2024 Academic Year.